2021
DOI: 10.1186/s41231-021-00091-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of parasitic infection on human gut ecology and immune regulations

Abstract: The human body harbors trillions of microbes collectively known as microbiota. The human gut microbiota is importantly involved in most of the human metabolic and regulatory pathways. The gut microbiota needs to be balanced for the health of the host. Several factors are involved in the distribution of microbiota in the human body, in most cases these microbiotas are commensals, but some circumstances lead to serious disorders and the development of infections from microbiota. When parasites colonize the gut, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 88 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…Previous studies have also indicated that the parasite Trichuris suis significantly affects the microbiota diversity in the colons of pigs. Moreover, the diversity and composition of the human gut microbiota has been found to be threatened by Necator americanus and other helminth parasites ( Naveed and Abdullah, 2021 ). In PA, host homeostasis was negatively affected by losses and shifts in the core microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also indicated that the parasite Trichuris suis significantly affects the microbiota diversity in the colons of pigs. Moreover, the diversity and composition of the human gut microbiota has been found to be threatened by Necator americanus and other helminth parasites ( Naveed and Abdullah, 2021 ). In PA, host homeostasis was negatively affected by losses and shifts in the core microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Dostal et al (2014) did not observe a significant effect on the gut microbiota in 6- to 11-year-old children living in South Africa following 38 weeks of iron supplementation (50 mg iron for 4 days/week) ( 23 ). These results highlight that study context is critical as many factors, including hygiene, diet, and parasite burden, can affect gut microbial composition ( 24 , 25 ). Furthermore, it is important to note that infant and childhood microbiomes are considered to be less stable and diverse than adult microbiomes ( 26 ).…”
Section: Discussionmentioning
confidence: 91%
“…Although some helminths can enhance the gut-barrier function, restrict bacterial translocation and induce a tolerogenic phenotype of resident muscularis macrophages, which are trained guardians of enteric neurons [ 126 , 127 ], virulent parasitic protozoa can have reverse effects, damaging the gut-barrier function and enteric neurons [ 128 ].…”
Section: Pathogens and Ens Development And Diseasementioning
confidence: 99%